ESCAPISM, THE NEED FOR AFFECT AND TRANSPORTATION AS PREDICTORS OF BINGE WATCHING IN UNIVERSITY STUDENTS - Ghania Atiq; Amber Baseer; Arooj Nazir (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study explored the factors that facilitate binge-watching behavior among young adults. Previous researches determined that escapism, need for affect and transportation can be considered as the predictors of binge-watching. To testify the existing literature on binge-watching and factors contributing to this behavior, 350 university students took part in a survey. Findings revealed that need for affect and transportation significantly predict binge-watching while escapism failed to predict binge-watching behavior due to non-significant results. Moreover, this study finds out that phenomenon of binge-watching has no significant impact on gender. Based on the findings, we propose that factors facilitating binge-watching i.e., need for affect and transportation can have adverse effects on students’ academic performance and mental well-being. Consequently, further researches need to adopt more holistic approach in investigating binge-watching and its effects.